PENGARUH PROFITABILITAS, NILAI PASAR, LIKUIDITAS DAN LEVERAGE TERHADAP HARGA SAHAM - Sandrika Widya Putri Setiawan; Ummi Kalsum; Belliwati Kosim (Sekolah Tinggi Ilmu Ekonomi Rahmaniyah Sekayu, 2023)
ABSTRACT This study aims to determine the effect of profitability, market value, liquidity, and leverage on stock prices in companies in the consumer goods industry sector which are listed on the IDX simultaneously and partially. The samples used in this study were 6 companies in the cosmetics and household goods sub-sector on the IDX for the 2017-2021 period using a purposive sampling method. This type of research uses quantitative research. The results of the study simultaneously show that profitability, market value, liquidity and leverage have a significant effect on stock prices. Partially, it shows that profitability (ROA) has a significant effect on stock prices, market value (EPS) has a significant effect on stock prices, liquidity (CR) has a significant effect on stock prices, and leverage (DAR) has no significant effect on stock prices. Keywords : Profitability, Market Value, Liquidity, Leverage, Stock Price